2017
DOI: 10.4103/0022-3859.194200
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological profile of chronic obstructive pulmonary disease

Abstract: Background:Different definitions used for chronic obstructive pulmonary disease (COPD) preclude getting reliable prevalence estimates. Study objective was to find the prevalence of COPD as per standard Global Initiative for Chronic Obstructive Lung Disease definition, risk factors associated, and treatment seeking in adults >30 years.Methodology:Community-based cross-sectional study was conducted in Delhi, among 1200 adults, selected by systematic random sampling. Pretested questionnaire was used to interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
27
1
2
Order By: Relevance
“…This study also indentified the prevalence among Bidi (filled with crude tobacco flake and mainly wrapped in a Piliostigma racemosum leaf) and cigarette smokers was 8.2 and 5.9%, respectively (Jindal et al, 2006 ). A recent cross sectional study was conducted among twelve hundred adults in Delhi, India (Sinha et al, 2017 ). This study suggested the prevalence of COPD was 10%, and the tobacco smoking adults were the strongest risk factor with this disease.…”
Section: Indian Prospectivementioning
confidence: 99%
See 2 more Smart Citations
“…This study also indentified the prevalence among Bidi (filled with crude tobacco flake and mainly wrapped in a Piliostigma racemosum leaf) and cigarette smokers was 8.2 and 5.9%, respectively (Jindal et al, 2006 ). A recent cross sectional study was conducted among twelve hundred adults in Delhi, India (Sinha et al, 2017 ). This study suggested the prevalence of COPD was 10%, and the tobacco smoking adults were the strongest risk factor with this disease.…”
Section: Indian Prospectivementioning
confidence: 99%
“…This study suggested the prevalence of COPD was 10%, and the tobacco smoking adults were the strongest risk factor with this disease. The old smoker had 63 % lesser risk as compare to current smokers (Sinha et al, 2017 ). Further, environmental smoke, occupational exposure, age factor, and biomass fuel are the others important factors which influence this health problem (Sinha et al, 2017 ).…”
Section: Indian Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…This distribution can be explained by the physiological decrease in FEV1 with age where the slope becomes steeper when aggravated by risk factors, particularly smoking. 5 The mean duration of COPD was 9.49±7.199 years.…”
Section: Discussionmentioning
confidence: 97%
“…3 In India, the prevalence of COPD has been reported at 3.49% (ranging from 1.1% in Mumbai to 10% in Thiruvananthapuram). 4,5 Bronchodilators continue to be the keystone of pharmacological treatment in patients with COPD. For the management of stable COPD; long-acting β 2 -agonists (LABA) and long-acting muscarinic antagonists (LAMA) are often preferred.…”
Section: Introductionmentioning
confidence: 99%